FACTORS THAT INCREASE BLOOD SUGAR IN JKN PATIENTS AT MUFID SIGLI HOSPITAL IN 2024 - M.Fathan Zhafran Ismy; Tri Makmur; Ismurrizal Ismurrizal; Muhammad Budi Syahputra (Poltekkes Kemenkes Bengkulu, 2025)
This study aims to identify the factors associated with increased blood sugar levels in JKN participants at RSU Mufid. A descriptive analytic approach with a cross-sectional design was used in this study, conducted at RSUD Mufid Kota Sigli from April to December 2024. The sample included 99 BPJS patients with Diabetes Mellitus (DM), selected using purposive sampling based on Slovin's formula with a margin of error of 10%. The study evaluated several risk factors, including physical activity, obesity, family history, hypertension, gender, and age. The results show that age over 40 years is the most dominant risk factor for increased blood sugar levels, with a prevalence ratio (PR) of 6.077. Hypertension also significantly contributes to increased blood sugar levels, with a PR of 5.742. Obesity, while having a smaller impact compared to age and hypertension, still contributes to the risk of diabetes mellitus, with a PR of 1.436. Therefore, diabetes prevention strategies should focus on weight management, blood pressure control, and the adoption of a healthy lifestyle, especially for individuals at higher risk.